Middle plane absorbed dose calculation applying in vivo dosimetry during total body irradiation - Ubillús, F. (2013)
Total Body Irradiation (ICT) with photon beams is a technique used in the treatment of haematopoietic diseases in order to achieve sterile conditions necessary to perform bone marrow transplants. For this dose should be prescribed in the plane of the patient and have a roughly accurate distribution of the dose (± 5 % deviation from the prescribed dose) throughout the body, but due to the irregular geometry of the patient can not use planning systems treatment, which is why it resorts to in vivo dosimetry. The application of the method of dosimetry in vivo is an algorithm based on the values of entry and exit doses measured by the detectors optically stimulated luminescence OSL (Al2 O3 :C) located on the surface of a phantom uniformity, which is irradiated with beams of 6 MV photons generated by the Siemens Primus Linear Accelerator Mid (Mevatron). Subsequently these results are compared with the dose readings taken by an ionization chamber (PTW-Freiburg TW31010 Model 2167) located in the middle plane. The same shall be for the case where the beam is attenuated by 22.72 %, using a lead shielding of 4 mm (used as protection of critical organs), checking deviations were less than ± 10 % in both cases. Therefore, the use of these detectors can develop an alternative dosimetric approach, which helps ensure the quality of treatment.